Effectiveness of extended producer responsibility policies implementation: The case of Portuguese and Spanish packaging waste systems. (10th February 2019) - Rubio, Sergio; Ramos, Tânia Rodrigues Pereira; Leitão, Manuel Maria Rodrigues; Barbosa-Povoa, Ana Paula
Abstract: European countries are attempting to promote sustainable development by transitioning from a linear to a circular economy, where waste is to be prevented and recycling activities are promoted. This paper studies the implementation of Extended Producer Responsibility (EPR) policies for the packaging waste in two later European adopter countries of waste management policies: Portugal and Spain. The main goal is to evaluate whether EPR policies in both countries have achieved their basic two goals: 1) reduction of waste, and 2) increase recycling activities. Two case-studies were built based on interviews made to main waste management stakeholders. The analysis shows that the implementation of the EPR policies have had a positive impact throughout the years in both countries. Regarding the waste reduction goal, the systems have still not been completely able to detach packaging waste production from economic growth, but they have been able to promote material usage reduction directly through the Green dot fee model adopted. Regarding the increasing of recycling activities, both countries have been able to increase such rates throughout the years, in the direction of the EU targets. Highlights: EPR policies implemented in Spain and Portugal are evaluated. EPR policies have contributed to packaging waste reduction and increase recycling activities. EPR policies are having a positive impact throughout the years in both countries. Some challenges still need to be faced: eco-design promotion and packaging life-cycle.